Pengaruh Informasi Manajemen, Sumber Daya Manusia , Sistem Dan Pegambilan Keputisan Terhadap Kinerja Pegawai Di Satuan Polisi Pamomg Praja - Ruray, Titiek Arafiani (Peneliti.net, 2025)
This research was conducted at the civil service police unit in the city of Tidore Islands. The sample taken in this research was 38 respondents. The data collection technique was by distributing questionnaires to respondents. This research uses descriptive analysis with a quantitative approach to test the level of reliability using Cronbach Alpha, then the data is processed using multiple linear regression analysis tests. Hypothesis testing uses Test with a significance level of 5%. This research uses SPSS Version 20 tools. The results of the multiple linear regression analysis test show that employee performance is influenced by system and HR variables. The test results explain that information and decision making variables do not have a significant effect on employee performance, while system and HR variables have a significant effect on employee performance. The results of the Determination test (R2) use an adjusted r square value of 0.540 or 54%. This shows that the independent variables (information, systems, human resources and decision making) can influence the dependent variable (employee performance) as seen from the R square of 58.9% and the remaining 41.1% is influenced by other variables that are not in this research.